Ontology of genesis of the general education course of Informatics in Russia based on historical and pedagogical analysis - Eteri V. Mindzaeva; Natalya I. Ryzhova (RUDN Journal of Informatization in Education)
Problem statement. In light of the decisions of the Ministry of Digital Development and Communications and the Ministry of Education of Russian Federation, it is planned to introduce a single textbook on computer science in Russian schools, which actualizes the problems of developing both the concept of teaching modern computer science to schoolchildren at all levels of basic general education, and updating the content of training in all generally recognized sections of the school computer science course, taking into account domestic innovations in the field of digital technologies and artificial intelligence, programming languages, software and computer technology. In this context, the development of concept of formation and development of the school general education subject “Informatics” from the standpoint of the historical and pedagogical approach is of particular importance. Methodology. The study was conducted using general scientific methods focused on the system of historical and pedagogical analysis of content of the stages of introduction of school computer science into Russian basic general education, based on empirical results of scientific and methodological research published over the past 40 years. Results. The article offers a substantive description of the main provisions of the historical and pedagogical approach to the study of the abovementioned issues, which represent the quintessence of ideas of various methodological approaches used in educational practice to systematize the history of formation of general education subject “Informatics” in the Russian school. The scientific novelty of the ideas and provisions of the proposed historical and pedagogical approach lies in the fact that the historical analysis is based on a view of the school computer science course as a pedagogical system of scientific and applied knowledge that determines the trends and features of the historical process of formation and development of school computer science in Russia. Conclusion. The historical and pedagogical approach, which provides opportunities to identify trends in the development of computer science didactics, makes it possible to predict the prospects for such development in the context of modern ideas and ongoing projects, primarily the project of creating a unified state textbook on Informatics.